Efficacy of the injury prevention program on football -Knee and trunk kinematics during anticipated and unanticipated side-step cutting - Saho, Y.; Suzuki, T.; Hoshiba, T.; Fukubayashi, T. (Sport Science Research, 2011)
The aim of this study was to investigate whether the injury prevention program would reduce the risk of knee ligament injury. Ten collegiate football players trained the injury prevention program, "The11", for 6 months. Prior and after intervention, subjects performed 3 maneuvers; a straight run, a sidestep cutting, and a crossover cutting, under two different conditions; anticipated and unanticipated. Using a target board with three LED, subjects were given cues for 1 of the 3 tasks in both the anticipated and unanticipated conditions. Subjects received the cue before the trial, for the anticipated trials. During unanticipated trials, subjects received visual cue approximately 500 msec before reaching step position. Three dimensional motion analysis system was used to measure knee and trunk motion during tasks. For this study, only the side-step cutting was analyzed. During anticipated task, the peak value of knee abduction angle after training was lower than before training (p<0.05). During unanticipated task, tibial internal rotation angle after training was lower than before training (p<0.05). Trunk orientation angles were not significant difference between before and after training (p<0.05). The results of this study indicated that The11 program has potential to change the knee motion to avoid the severe knee injuries.